Fragmentation of vegetation in protected area in the cerrado region (Research, Society and Development, 2021)
The vegetation of the Cerrado biome has suffered severe degradation by the expansion of farming and lack of protected areas. Thus, studies that assist in the decision making management of protected areas become increasingly important. Thus, the aim of this study was to assess the fragmentation of vegetation in the Parque Natural Municipal Salto do Sucuriú region. The study area is part of the Biodiversity Corridor Emas-Taquari, demonstrating the importance of analyzing this region using geotechnologies. Furthermore, it was analyzed the fragmentation of vegetation being produced Land Cover Letter (with the quantification of the area occupied by each of the 10 classes of soil cover), Letter of Evaluation Index of the Fragments by Edge (which allowed an assessment of the shape of the remaining vegetation patches on a vulnerability scale - 5 classes) and the Letter of Evaluation of fragments by size (showing that the small patches of native vegetation are numerous, but that there are still two large fragments in the landscape). All these data describe the structure of the landscape of the region and the relationship of the number, shape and size with the remaining biodiversity, energy and matter present in the region. Thus, through the use of geotechnology results were produced in a region that has a conservation unit. Repeating the method presented in this study, at regular time intervals, allows monitoring of the environmental situation in the region this important conservation unit, serving as a management tool for environmental agencies.